Deep Learning Algorithms and Applications in Computer Vision - Shetty, Savita K; Siddiqa, Ayesha (International Journal of Computer Sciences and Engineering, 2019)
Deep Learning is a system powered by huge amounts of data. With the generation of massive amounts of data, the data analysing keeps getting complex. Deep learning solves the problem of Traditional ML algorithms that fail to perform well when the amount of data is enormous. Deep learning can be applied to any type of data such as text, image and so on. Deep learning algorithms generally used and best suited for image data are DBN and CNN. Analysing Computer vision using CNN brings a lot of use cases such as detection, recognition from the images, which can be useful in many fields such as medical images to detect a tumour and recognize its type, or help a robot navigate by identifying obstacles. In this paper we discuss what is Artificial Intellignece(AI), Machine Learning(ML) and Deep Learning and explore some of the Deep learning algorithms. We also understand how CNN can be applied in different applications of Computer vision and study the three major applications of Computer vision which are Image captioning, Medical image analysis and Robots Navigation.